HUBUNGAN ANTARA KETERLAKSANAAN PRAKTIKUM FISIKA DASAR 1 MENGGUNAKAN VIDEO DENGAN KETERAMPILAN PROSES SAINS (KPS) PADA PEMBELAJARAN DARING - Jusman, Jusman; Dhea Anggreny; Abrar, Andi Ika Prasasti (UIN Alauddin Makassar, 2022)
The aims of this study were to: 1) to determine the implementation of practicum using video during online learning in the basic physics experimental course 1 class of 2020 physics education at UIN Alauddin Makassar, 2) to find out the science process skills (KPS) of students in the experimental course. basic physics 1 class 2020 physics education UIN Alauddin Makassar, 3) to find out whether there is a relationship between the implementation of physics practicum using video and science process skills (KPS) in online learning for the basic physics experimental course 1 class 2020 UIN Alauddin Makassar. The type of research is Ex post facto research with correlation design. The results showed that 1) The description of the implementation of physics practicum using video for physics education students batch 2020 was in the medium category with an average result of 20.35, 2) The description of science process skills in physics education students batch 2020 was in the low category with results an average of 43.88, 3) there is no significant relationship between the implementation of physics practicum using video with science process skills. This can be seen from the results of the Spearman rank correlation analysis, namely the data t count < t table.